Basic and morphological properties of Bukit Goh bauxite - Muzamir, Hasan; Ahmad Amirul Faez, Ahmad Nor Azmi; Weng, Long Tam; Biao, Yu Phang; Moqsud, M. Azizul (IOP Publishing, 2018)
Investigation conducted by International Maritime Organization (IMO) concluded that the loss of the Bulk Jupiter that carrying bauxite from Kuantan has uncovered evidence to suggest liquefaction led to loss of stability. This research analysed Bukit Goh bauxite and comparison was made with International Maritime Solid Bulk Cargoes (IMSBC Code) standard. To analyse these characteristics of the bauxite, four samples were selected at Bukit Goh, Kuantan ; two of the samples from the Bukit Goh mine and two samples from the stock piles were tested to identify the bauxite basic and morphological properties by referring to GEOSPEC 3 : Model Specification for Soil Testing ; particle size distribution, moisture content and specific gravity and its morphological properties. Laboratory tests involved including Hydrometer test, Small Pycnometer test, Dry Sieve test and Field Emission Scanning Electron Microscop (FESEM) test. The results show that the average moisture content of raw Bukit Goh bauxite is 20.64% which exceeded the recomended value of maximum 10%. Average fine material for raw bauxite is 37.75% which should not be greater than 30% per IMSBC standard. By that, the bauxite from Bukit Goh mine do not achieved the minimum requirements and standards of the IMSBC standard and need to undergo beneficiation process for better quality and safety.